A Case Report of Spontaneous Lesser Omental Haemorrhage. Issue 1 (January 2015) - Zhu, Jg; Zhang, Zt; Zhao, N; Zhang, Hm; Han, W
Spontaneous rupture of the lesser omental artery in the absence of identifiable causes is rare. We describe a case of abdominal apoplexy secondary to a spontaneous lesser omental artery rupture. A 73-year-old woman presented to our emergency department for acute abdominal pain with persistent nausea and vomiting. Abdominal examination revealed mild epigastric tenderness but no signs of peritonitis. Computed tomography of the abdomen suggested a massive volume of blood in the peritoneal and pelvic cavity. The diagnosis was made by exploratory laparotomy revealing haemoperitoneum, a haematoma in the lesser omentum near the antrum with an active bleeder. Choices of investigation modality for diagnosis and treatment are discussed. (Hong Kong j.emerg.med. 2015;22:53-56)